The effect of static stretching warm-up and dynamic stretching warm up on speed and agility among youth football players / Muhammad Azwar Mazlan - Mazlan, Muhammad Azwar (2014)
Stretching and warm up session is one of important aspect before an athlete begin any physical activity in order to make the body ready for any upcoming activity. Different Warm up protocol can influence the athlete performance. Purpose: The purpose of this study is to compare the effects of dynamic stretching warm-up and static stretching warm up on speed and agility performance among youth football players. Thirty football player aged 15 - 17 years old were recruited from Yayasan Negeri SembiIan Football Academy. Subjects are randomly divided into two, static group and dynamic group. Each group will perform the 30 Meter Dash and lllinios Agility Test. All data were analyzes using SPSS version 20 statistical software. The results shown there were significant different in 30 Meter Dash (p< 0.017) between two group. However, result shown no significant different in Illinios Agility Test (p > 0.088). As a conclusion, dynamic stretching may improve speed performance among football players.